ANALISIS KORELASI ANTARA BIAYA KUALITAS DAN BIAYA DISTRIBUSI TERHADAP PROFITABILITAS PADA PT SEMEN INDONESIA PERSERO (TBK) - - Mafazatun; Evaliati Amaniyah; Prasetyo Nugroho (Eco-Entrepreneur, 2017)
The purpose of study are (1) to know there is any correlation between the cost of the quality with ROA in PT. Cement Indonesia Persero (Tbk), (2) to know there is any correlation between the cost of the quality with ROE in PT. Cement Indonesia Persero (Tbk), (3) to know there is any correlation between the cost of distribution with ROA in PT. Cement Indonesia Persero (Tbk), (4) to know there is any correlation between the cost of distribution with ROE in PT. Cement Indonesia Persero (Tbk). This study use correlation analysis to test the hypothesis. The result of this study indicate that (1) correlation between the cost of the quality of with ROA is -0,990. It means that correlation between the cost of the quality of with ROA in the category of negative strong. (2) correlation between the cost of the quality of with ROE is -0,892. It means that correlation between the cost of the quality of with ROE in the category of negative strong. (3) correlation the cost of the distribution of with ROA is -0,923. It means that correlation between the cost of the distribution of with ROA in the category of negative strong. (4) correlation between the cost of the distribution of with ROE is -0,964. It means that correlation between the cost of the distribution of with ROE in the category of negative strong.